1999
DOI: 10.1128/jvi.73.6.4882-4889.1999
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Major Neutralizing Epitope on Human Papillomavirus Type 16 L1

Abstract: Persistent infection with human papillomavirus type 16 (HPV-16) is strongly associated with the development of cervical cancer. Neutralizing epitopes present on the major coat protein, L1, have not been well characterized, although three neutralizing monoclonal antibodies (MAbs) had been identified by using HPV-16 pseudovirions (R. B. Roden et al., J. Virol. 71:6247–6252, 1997). Here, two of these MAbs (H16.V5 and H16.E70) were demonstrated to neutralize authentic HPV-16 in vitro, while the third (H16.U4) did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 24 publications
(35 reference statements)
0
71
0
1
Order By: Relevance
“…Both linear and conformational epitopes have been identified on the surface of HPV L1 VLPs [9,10,18,39,41,44]. It is now well established that conformational epitopes are responsible for neutralizing antibody production [7,14,21,42,43]. Since neutralization epitopes of HPVs are conformation-dependent, their amino-acid composition and surface localization have not been fully characterized, and studies have been mainly limited to types 6, 11 and 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both linear and conformational epitopes have been identified on the surface of HPV L1 VLPs [9,10,18,39,41,44]. It is now well established that conformational epitopes are responsible for neutralizing antibody production [7,14,21,42,43]. Since neutralization epitopes of HPVs are conformation-dependent, their amino-acid composition and surface localization have not been fully characterized, and studies have been mainly limited to types 6, 11 and 16.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-HPV monoclonal antibodies have been generated against the L1 protein of different human papillomavirus types, and they have been used to map the neutralization epitopes for types 6,11,16, and 31 [4,[24][25][26]43].All conformationdependent monoclonal antibody epitopes identified to date are type-specific and have been found to reside on the VLP surface within hypervariable loops, with the exception of the H16.U4 MAb, which was recently demonstrated to bind the C-terminal arm of HPV-16 L1 between residues 427 and 445 [4]. L1 binding sites of neutralizing monoclonal antibodies raised against L1 VLPs include residues within the DE loop for type 11 [24,25], residues within BC and EF loops for type 6 [27], and residues within the FG loop for type 16 [30,32,43]. Only one MAb (H31.A6) has been produced for HPV-31 [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to be protective these antibodies must target conformational neutralizing epitopes on the viral capsid proteins. Major neutralizing epitopes have been found on the HPV16-L1 coat protein [23]. Therefore antibodies to these epitopes might be involved in the development of protection against HPV16 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the opposite approach (immobilizing the large binding partner on the sensor chip surface) permits the screening of panels of cell and virus ligands. Using this approach, Powell et al 447 and White et al 448 identified and characterized virusrecognizing receptors and antibodies. Bousquet et al used SPR to examine the interaction of suspended nanoparticles with immobilized human serum albumin as an initial phase in the development of polymer nanoparticles applicable for injection and ingestion to aid in the delivery and dispensing of drugs in the body.…”
Section: Large Particlesmentioning
confidence: 99%
“…Ninety-percent of the 1999 publications reported using BIACORE technology (Biacore AB, Uppsala, Sweden); 1-457 8% reported using IAsys (Affinity Sensors, Franklin, MA); and 2% reported using other instruments, including IBIS (Windsor Scientific Limited, Berks, UK), 507 SPR-670 (Nippon Laser and Electronics Laboratory, Hokkaido, Japan), 499,500,504,506 TISPR-1 (Texas Instruments, Dallas, TX), 497,501 and an instrument produced by Johnson & Johnson Orthoclinical Diagnostics Ltd (Chalfont St Giles, UK). 498,502,503,505 Given the large number of publications describing the use of BIACORE technology, these references are subdivided into the following categories: reviews, 1-10 methods, 11-16 mass transport, 17-22 antibodies, 23-102 proteins, 103-203 cell surface receptors, extracellular matrix, peptides, oligonucleotides, carbohydrates, [389][390][391][392][393][394] small molecules, lipids, 416-442 cells and particles, [443][444][445][446][447][448] complex analytes [449][450][451][452][453][454] and other systems. [455][456][457]…”
Section: Introductionmentioning
confidence: 99%